Perbandingan Efektivitas Media Video dengan Paper sebagai Skenario terhadap Capaian Tahapan Seven Jump pada Blok Kedokteran Tropis dan Penyakit Infeksi PPD UNPATTI - , johan bruiyf bension, Dra. Yayi Suryo Prabandari, M.Si., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. In a teaching learning process, there are two elements that are very important, teaching method and learning media. The role of media is highly needed since it has big role in achieving the goal of learning. In tutorial process using the stages of seven jump, the scenario that is commonly used is paper case form. Video scenario can be better since video has several advantages. This makes the video scenario can be used for teaching learning process effectively. Objective. This research aims to compare the effectiveness of video scenario to paper in achieving the seven jump stages in the tutorial. Research method. This is a quantitative research with experiment method and design of posttest only with control group design. The subject of the research was the whole tutorial discussion group of sophomore of Doctor Education Program (Program Pendidikan Dokter) UNPATTI with the total amount of 50 students. The data was collected and analyzed using statistical test to find out certain treatment to other variables. Result. The result of independent sample t-test showed the value p < 0.05, which means there was significant difference. Based on the p value (0.016) < 0.05, it can be concluded that there was difference between the mean of scores achieved by seven jump in the tutorial groups of discussion using the video scenario and the paper case scenario, with the score of achievement of seven jump stages with video scenario was higher than the achievement score of seven jump stages using paper case scenario.